Pengaruh Terapi Dzikir terhadap Intensitas Nyeri pada Pasien Gastritis - Fadli Fadli; Resky Resky; Andi Sastria (Jurnal Kesehatan, 2019)
The digestive system is a food/nutrition pathway from the entrance or input to output (excretion/elimination). Anatomically the digestive system or often called the digestive or gastrointestinal system consists of various kinds of organs from the oral cavity to the anus. Complaints in gastrointestinal patients can be related to local/intralumen disorders of the gastrointestinal tract for example the presence of duodeni ulcers, gastritis and so on. The purpose of this study was to determine the effect of dzikir therapy on pain intensity in gastritis patients. The study used a quasy experiment design with the Pre and Post Test Group design approach. This research was conducted from June to August 2018. Data collection in the Surgical Room of Nene Mallomo Hospital, Sidrap Regency was conducted every morning starting June 2, 2018 to August 25, 2018 with a total sample of 45 respondents. The results of this study found that p=0,000 with a significance level of p <α (0.05) where p <α so can be concluded that there is an effect of dzikir therapy on pain intensity in gastritis patients at Nene Mallomo Hospital, Sidrap Regency.